Impact of Transformer Grounding On TRV During Inductive Load Switching at Transmission and Substation Service Unit (ULTG) Maros - Khaidir, Muhammad; Sriwati; Saktiani Karim; Faridah; Fadhli Rahman; Syarifuddin Baco (Jurusan Teknik Elektro Universitas Andalas, 2026)
This paper investigates the impact of transformer grounding configurations on Transient Recovery Voltage (TRV) during fault current interruption in high-voltage power systems. The study evaluates three grounding schemes: Solid–Solid, Solid–Floating, and Solid–Resistance, applied on a step-down transformer located at the Tello substation. Each configuration was modeled and simulated using ETAP 19 software to observe TRV behavior under three-phase fault conditions. The results demonstrate significant variations in TRV profiles depending on the grounding type. The Solid–Solid configuration exhibits the highest TRV peak (22,500 V) and the steepest Rate of Rise of Recovery Voltage (RRRV), reaching 833.33 kV/ms, indicating severe stress on circuit breaker insulation. In contrast, the Solid–Floating configuration yields a moderate TRV peak (19,800 V) with less consistent waveform stability due to the absence of a defined secondary reference. Meanwhile, the Solid–Resistance scheme, using a 20 Ω resistor, produces the most damped TRV waveform with the lowest peak (17,100 V) and RRRV (approximately 589.66 kV/ms), offering improved insulation coordination. The comparative analysis confirms that controlled grounding through resistance effectively mitigates TRV magnitude and oscillation, making it a viable approach to enhance circuit breaker performance and reliability. These findings can be used to guide grounding system design in high-voltage substations to reduce the risk of re-ignition or insulation failure.